AnaIisis Kepuasan Pelanggan Pada AnaIisis Kepuasan Pelanggan Pada E-Commerce Shopee Dengan Metode UTAUT: Perdagangan Elektronik, Shopee, UTAUT, Kepuasan Pengguna - herlina margaretha (CogITo Smart Journal, 2023)
Advances in technology make it easier to carry out activity. Example of this activity is online shopping. Shopee is one of Indonesia's leading e-commerce sites. An e-commerce must be able to ensure that the system can run well without disturbing or making difficult for users so as to increase user satisfaction. This study aims to determine how to analyze customer satisfaction on Shopee with the UTAUT method. The UTAUT modeI has various categories such as, performance. expectancy, effort. expectancy, sociaI infIuence, and faciIitating. conditions. UTAUT is useful for explaining how users pay attention to their use of information systems and their behavior. The results of this study are using SPSS, validity and reliability tests will be carried out and through hypotheses which will be tested with t statistical tests. Analysis of Shopee's information technology on customer satisfaction with UTAUT method is important to find out the problems of Shopee system that harm users and even the system itself. This paper shows that each independent variable, performance. expectancy, effort. expentancy, social infIuence, and faciIitating conditions has a positive and significant result towards dependent variable, Shopee customer satisfaction in using the Shopee.